2001
DOI: 10.2337/diacare.24.5.865
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Blood Mitochondrial DNA Content Is Related to Insulin Sensitivity in Offspring of Type 2 Diabetic Patients

Abstract: OBJECTIVE -To investigate whether the peripheral blood mtDNA (pb-mtDNA) content is decreased and linked to insulin resistance in the offspring of type 2 diabetic patients.RESEARCH DESIGN AND METHODS -A total of 82 offspring of type 2 diabetic patients and 52 age-, sex-, and BMI-matched normal subjects from the Mokdong, Korea, population were selected for this study by stratified, randomized sampling. Of the offspring of diabetic patients, 52 had normal glucose tolerance (NGT), 21 had impaired glucose tolerance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
93
2
2

Year Published

2001
2001
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 124 publications
(108 citation statements)
references
References 22 publications
11
93
2
2
Order By: Relevance
“…In both obesity and common forms of type 2 DM, glucose oxidation and storage are reduced, in parallel with reduced activity of tricarboxylic acid cycle, ␤-oxidation, and electron transport enzymes (29). Moreover, reductions in mitochondrial area (30), number (31,32), and complex I activity correlate with decreased insulin-stimulated glucose disposal (30). Our data provide a potential molecular mechanism for these results (Fig.…”
Section: Discussionmentioning
confidence: 68%
“…In both obesity and common forms of type 2 DM, glucose oxidation and storage are reduced, in parallel with reduced activity of tricarboxylic acid cycle, ␤-oxidation, and electron transport enzymes (29). Moreover, reductions in mitochondrial area (30), number (31,32), and complex I activity correlate with decreased insulin-stimulated glucose disposal (30). Our data provide a potential molecular mechanism for these results (Fig.…”
Section: Discussionmentioning
confidence: 68%
“…Interestingly, Song et al [13] found that patients with diabetic complications have an 'atypical increase in mtDNA copy number'. As monocyte populations are now recognised to be heterogeneous [34] and different monocyte populations can independently predict vascular disease [35], it is possible that monocytes in patients with diabetes complications have a different biology to those in patients without complications.…”
Section: Discussionmentioning
confidence: 99%
“…As previous studies have indicated an age-related decline in mtDNA content, we sought to reduce the confounding impact of age by studying only patients aged ≥50 years [13]. Patients were excluded if taking HIV medications or had a known haematological malignancy.…”
Section: Patientsmentioning
confidence: 99%
“…4 In this respect, qualitative and quantitative changes in mitochondrial DNA (mtDNA) were involved in the pathogenesis of type 2 diabetes, particularly when the changes occur in the skeletal muscle. 5 Moreover, the mtDNA content in peripheral blood leukocytes has been associated with IR in children and adults, 6,7 and is an early event observed in small-and large-for-gestational-age newborns. 8 Consistent with these observations, mitochondrial dysfunction also plays a significant role in the pathogenesis of NAFLD, 9 suggesting that both IR and NAFLD share several morphological and functional abnormalities.…”
mentioning
confidence: 99%